Market Liquidity, Investor Participation and Managerial Autonomy: Why do Firms go Private? - Arnoud W.A. Boot; Radhakrishnan Gopaian; Anjan V. Thakor (Tinbergen Institute, 2006)
We analyze a publicly-traded firm's decision to stay public or go private when managerial autonomy from shareholder intervention affects the supply of productive inputs by management. We show that both the advantage and the disadvantage of public ownership relative to private ownership lie in the liquidity of public ownership. While the liquidity of public ownership lets shareholders trade easily and supply capital at a lower cost, the liquidity-engendered trading also results in stochastic shocks to a firm's shareholder base. This exposes management to uncertainty regarding the identity of future shareholders and their extent of intervention in management decisions and in turn curtails managerial incentives. By contrast, because of its illiquidity, private ownership provides a stable shareholder base and improves these inputprovision incentives but results in a higher cost of capital. Thus, capital market liquidity, while being a principal advantage of public ownership, also has a surprising 'dark side' that discourages public ownership. Our model takes seriously a key difference between private and public equity markets in that, unlike the private market, the firm's shareholder base, namely the extent of investor participation, is stochastic in the public market. This allows us to extract predictions about the effects of investor participation on the stock price level and volatility and on the public firm's incentives to go private, thereby providing a link between investor participation and firm participation in public markets. Lesser investor participation induces lower and more volatile stock prices, encouraging public firms to go private, whereas greater investor participation encourages younger firms to go public. Moreover, IPO underpricing is optimal because it is shown to lead to a higher and less volatile post-IPO stock price, greater autonomy for the manager and a higher supply of privately-costly managerial inputs.
Keywords: G24; G10; G32; 330; Corporate Finance; Unternehmen; Eigentümerstruktur; Börsengang; Börsenrückzug; Corporate Governance; Betriebliche Liquidität